Obstacle Factors on Evidence System of Urine Test Result on Drugs Cases in National Narcotics Board of North Sumatera Province, Indonesia - Zulyadi, Rizkan (Budapest International Research and Critics University, 2020)
This study aims to discuss what factors inhibit the system of proving the results of urine test narcotics cases in the National Narcotics Agency of North Sumatra Province. the system of proving urine test results in narcotics cases in the National Narcotics Agency of North Sumatra Province that the opinion of Dr. Romi as a medical team at BNN said the function of the urine test is to determine whether or not someone has used narcotics because in the urine it will be known whether there is a narcotic content or not that can only be known for 1-7 days after use and urine tests are carried out with aids in the form of stick test. Provide counseling about Narcotics and the presence of BNN in North Sumatra Province in educational institutions. Provide counseling about Narcotics and the presence of BNN in each region in the Province of North Sumatra as a research location. Establish cooperation with parties both public and private to provide counseling in each institution.